2017
DOI: 10.1175/jpo-d-16-0192.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of 3D Vertical Circulation in the Upwelling and Frontal Zones East of Hainan Island, China

Abstract: Using the generalized omega equation and cruise observations in July 2012, this study analyzes the 3D vertical circulation in the upwelling region and frontal zone east of Hainan Island, China. The results show that there is a strong frontal zone in subsurface layer along the 100-m isobath, which is characterized by density gradient of O(10−4) kg m−4 and vertical eddy diffusivity of O(10−5–10−4) m2 s−1. The kinematic deformation term SDEF, ageostrophic advection term SADV, and vertical mixing forcing term SMIX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The wind-forced offshore Ekman transport is the general mechanism for the coastal upwelling [16,[19][20][21]. In recent decades, with global climate change, the long-term and interannual variability of upwelling, particularly its response to extreme events, such as the El Niño-Southern Oscillation (ENSO) events, has been paid more and more attentions [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wind-forced offshore Ekman transport is the general mechanism for the coastal upwelling [16,[19][20][21]. In recent decades, with global climate change, the long-term and interannual variability of upwelling, particularly its response to extreme events, such as the El Niño-Southern Oscillation (ENSO) events, has been paid more and more attentions [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, upwelling east of Hainan Island (UEH) is seasonal coastal upwelling in the northwestern South China Sea (SCS). It occurs mostly within a range of 40 km off the coastline in summer months as the southwesterly monsoon prevails [16,21,32]. The wind-driven offshore Ekman transport and Ekman pumping, as well as the topography effect, are main mechanisms of the UEH [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its energy dissipation mechanism has attracted attention for a long time (Ferrari & Wunsch, ). The ocean front has an important effect on turbulence mixing in the upper ocean (Xie et al, ). Recent field observations have shown that the turbulent kinetic energy (TKE) dissipation rates within the ocean surface boundary layer can be elevated by about 2 orders of magnitude by the Kuroshio front (D'Asaro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The major circulation of the SCS is driven by the monsoon wind [8], with a southward coastal current along the western boundary in the winter and a northward coastal current in the summer [9,10]. Concerning regions around Hainan Island, many previous studies have focused on the summertime upwelling systems off the east coast (e.g., [11][12][13]). For example, the work of Su and Pohlmann [13] revealed that the southwesterly and southerly winds in the summer are responsible for the formation of the cold water centers off the eastern Hainan coast, while the combined effects of wind and topography lead to the uneven distribution of the upwelling centers.…”
Section: Introductionmentioning
confidence: 99%